Determining the Bulk Growth, Nucleation Kinetics, Optical and Spectral Analysis of Organic Nonlinear Material: 4-Chloroaniline (pCA) Single Crystal - M. Vijayalakshmi; R. Ezhil Vizhi; D. Rajan Babu (Recent Trends in Chemical and Material Sciences Vol. 5, 2022)
Slow cooling was used to form a single crystal of the organic nonlinear optical substance 4-chloroaniline (pCA). Gravimetric analysis was used to assess the material solubility and the metastable zonewidth MSZW was measured at various temperatures. The values of the induction period were calculated for various supersaturation ratios and temperatures. Experimentally obtained induction period values were used to calculate the interfacial energy. Theoretically, the energy results were compared to experimental values determined from the solubility data. The nucleation parameters were determined including Gibb’s free energy change, critical nuclei radius, number of molecules present in the nuclei and nucleation rate. X-ray diffraction analysis was used to estimate the unit cell characteristics. The UV-Vis-NIR spectrum was used to examine the transmission properties of the pCA crystal. FT-Raman spectrum analysis was used to identify the various vibrational modes of different functional groups and assign wavenumbers to them. The nonlinear optical property of the grown crystal was measured using a Q-Switched Nd: YAG laser and the efficiency was evaluated by comparing to that of standard KDP.